2016
DOI: 10.3329/ptcb.v26i2.30574
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Indigenous Lipase Producing Bacteria from Lipid?rich Environment

Abstract: To isolate and characterize lipase producing bacteria from lipid-rich environment and screen the best lipolytic indigenous bacteria a study was made. For the isolation of bacteria, oil based wastewater and soil were collected from ten different sampling sites.Four different media were used for study the aerobic heterotrophic bacterial count. The highest bacterial count (1.56 × 10 7 cfu/gm) was observed in dairy farm soil and lowest (8.3 × 10 2 cfu/ml) in the Buriganga river water. The highest percentage (94.51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…However, the PCR-molecular weights of the isolates were within the range of 410 and 450 base pairs. There was no recognizable alteration with the report of [27], who recorded that PCRmolecular weight of Bacillus cereus was 475 base pairs which were also similar to [25] whose report documented molecular weight of about 500 base pairs. The findings of [40] differed with the result of this investigation as the PCRmolecular weight was 900 base pairs.…”
Section: Bioinformatics Studies Of Aab Isolatessupporting
confidence: 73%
See 2 more Smart Citations
“…However, the PCR-molecular weights of the isolates were within the range of 410 and 450 base pairs. There was no recognizable alteration with the report of [27], who recorded that PCRmolecular weight of Bacillus cereus was 475 base pairs which were also similar to [25] whose report documented molecular weight of about 500 base pairs. The findings of [40] differed with the result of this investigation as the PCRmolecular weight was 900 base pairs.…”
Section: Bioinformatics Studies Of Aab Isolatessupporting
confidence: 73%
“…From this study, Bacillus cereus and Stenotrophomonas maltophilia are the two unique bacterial isolates characterized using 16S DNA sequencing approach with accession number MK 332142 and MK 332143, respectively. In addition, [25] had a stern agreement with the outcomes of this study having documented that his routinely identified Acetobacter sp., which was later determined and identified through molecular analysis had attributes similar to that of our Stenotrophomonas maltophilia. Furthermore, this study thus corroborates with the findings of [25] since he ascertained the presence of both Stenotrophomonas maltophilia and Bacillus cereus from lipase rich substrates.…”
Section: Bioinformatics Studies Of Aab Isolatessupporting
confidence: 55%
See 1 more Smart Citation
“…It has recently been shown that lipolytic microorganisms are present in lipid-rich industrial wastewater (dairy [ 6 ], chocolate factory [ 7 ], fish-canning [ 8 , 9 ]), as well as in domestic effluent [ 10 , 11 ] and landfill leachate [ 12 ]. Furthermore, in samples from ten environments historically polluted by lipid-containing wastewater, [ 13 ] found the highest concentration of lipase-producing bacteria in soil contaminated by edible oil (EO) industry wastewater. These studies were limited to the investigation of fast-growing fungi and bacteria (mostly Enterobacteriaceae and Bacillus species), with slower-growing microorganisms, such as actinobacteria, being excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Among microbial lipases bacterial lipases are more economical and stable (3). Most of the Bacterial species secretes lipase extracellular which are majorly affected by nutritional and physicochemical factors such as temperature, pH, nitrogen source and carbon source, inorganic salts, agitation and DO concentration (11,12,13,14).Media containing lipidic carbon, like edible and non-edible oils, fatty acids, glycerol or tweens in the presence of an organic nitrogen source facilitates the lipase production (15). Among many species some of them are efficient extracellular lipase producers mainly Achromobacter, Alcaligenes, Arthrobacter, Pseudomonas, Staphylococcus, Chromobacterium, Bacillus and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%